"Ollas" urban phenomenon : from urban decay to the revitalization of high complexity areas in the city of Bogotá. Approach to a model of urban and architectural strategies for the analysis and intervention of deteriorated territories for their reintegration into the urban life (2020)
The cities are composed by a series of complex networks of relationships that shape an urban fabric based on the social condition developing around the territory. The urbanism that rules most human establishments today, can be clearly differentiated by the conditions in which the inhabitants have appropriated the spaces that constitute the urban centers. In the case of the city of Bogotá, the contrasting territory is notorious. The capital district stands as the largest urban center in the country, which has a great historical, economic, and social burden and yet stands out strongly for its anti-value of urban deterioration. Within the rest of the city, some sectors coexist despite of being on undergoing process of deterioration because of urbanistic and social reasons that determined the spatialization of the crime and marginal dynamics. This issue has spread and become more complex over time. The areas called “ollas”, remind the city the consequences of oblivion and indifference toward broken zones, and at the same time, set an opportunity to transform the urban environment through architectural actions.